Chromatin Condensation Variation during Confined Cell Migration - Sarasquete Martinez, Maria; de Corato, Marco; Gómez Benito, Mª José (Jornada de Jóvenes Investigadores del I3A, 2023)
Cells are subjected to a spectrum of mechanical cues to which they adapt. We use microfluidic devices to simulate their mechanical environment during confined migration. We found that chromatin condensation differs according to the degree of confinement.